2015
DOI: 10.1016/j.neuron.2014.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Coupling to Feedback Inhibition during a Critical Period for the Integration of Adult-Born Granule Cells

Abstract: SUMMARY Developing granule cells (GCs) of the adult dentate gyrus undergo a critical period of enhanced activity and synaptic plasticity before becoming mature. The impact of developing GCs on the activity of preexisting dentate circuits remains unknown. Here we combine optogenetics, acute slice electrophysiology, and in vivo chemogenetics to activate GCs at different stages of maturation to study the recruitment of local target networks. We show that immature (four-week-old) GCs can efficiently drive distal C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
239
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(247 citation statements)
references
References 69 publications
6
239
0
2
Order By: Relevance
“…Learning itself has been studied with optogenetics in ventral striatum and amygdala 143,144 , as well as in the hippocampus 138 , and inputs to the hippocampal formation have been studied in some detail with regard to causal roles in learning, navigation and information flow 145147 . Finally, precisely timed activity patterns in diverse well-defined cell types, projections and populations have been causally implicated in synaptic plasticity 148,149 , wiring and microcircuit plasticity 150,151 , and in long-timescale devel-opmental 152,153 and adaptive changes such as activity-dependent myelination 154 and adult neurogenesis 155,156 .…”
Section: Discoveries With Optogeneticsmentioning
confidence: 99%
“…Learning itself has been studied with optogenetics in ventral striatum and amygdala 143,144 , as well as in the hippocampus 138 , and inputs to the hippocampal formation have been studied in some detail with regard to causal roles in learning, navigation and information flow 145147 . Finally, precisely timed activity patterns in diverse well-defined cell types, projections and populations have been causally implicated in synaptic plasticity 148,149 , wiring and microcircuit plasticity 150,151 , and in long-timescale devel-opmental 152,153 and adaptive changes such as activity-dependent myelination 154 and adult neurogenesis 155,156 .…”
Section: Discoveries With Optogeneticsmentioning
confidence: 99%
“…This idea is based on empirical data showing that activation of adult-born GCs selectively, using optogenetics, causes both inhibition and excitation of other GCs (Drew et al, 2013). Previous studies also have shown that during maturation, adult-born GCs display a dynamic set of intrinsic and synaptic characteristics that make them vary their role in the DG-CA3 circuitry (Dieni et al, 2013; Temprana et al, 2015). …”
Section: Dominant Gcs Mossy Fiber Variance and Their Implicationsmentioning
confidence: 99%
“…He also presented recently published (Temprana et al, 2015) and unpublished data using optogenetics and chemogenetics to map the local target networks activated by adult-born neurons. Shaoyu Ge (Stonybrook University, New York, USA) continued the theme of circuit-level analysis by defining the mechanisms that control the initiation of circuit integration of adult-born neurons.…”
Section: Functional Implications Of Adult Neurogenesis At the Circuitmentioning
confidence: 99%